Mucositis Effect on Quality of Life of Hospitalized Children with Cancer Who Received Chemotherapy - Sri Hendrawati; Ikeu Nurhidayah; Henny Suzana Mediani; Ai Mardhiyah; Nenden Nur Asriyani Maryam (Jurnal Keperawatan Padjadjaran, 2019)
Mucositis is very common in children with cancer who received chemotherapy. Mucositis in children renders other health problems such as pain, eating problems, insomnia, and emotional problems that directly determine children’s quality of life. The purpose of this research was to identify how the effects of mucositis on quality of life in children with cancer who received chemotherapy. The method used in this research is correlative descriptive analytic with cross-sectional design. Samples taken in this research utilized consecutive sampling technique. The children with cancer who met the inclusion criteria were approached to participate in this research. Sixty children with cancer hospitalized in Dr. Hasan Sadikin Hospital Bandung recruited in this research. Mucositis identification utilized Oral Assessment Guide (OAG). Data quality of life (QoL) would be assessed with PedsQoL Cancer Module 3.0. Data were analyzed by Chi-square correlation test. There are 53 children (88.3%) who experienced mucositis. In contrast, there are only 7 children who didn’t experience mucositis (11.7%). Based on this survey, there are 37 children (61.7%) have bad quality of life. Otherwise, 23 children (38.3%) have good quality of life. This research found that there is a significant relationship between mucositis and QoL of children with cancer. Accordingly, the relationship between mucositis cases and QoL of children with cancer valued at 0.006 (p<0.05). Mucositis cause low QoL in children with cancer compared to them without mucositis. Nurse should increase nursing care for children with mucositis as the side effect of chemotherapy. Suggested efforts are to prevent mucositis complication that will impact QoL, such as giving oral care with honey, keeping humid oral mucosa, and preventing infection